Mono-N-alkylation of Amphotericin B and Nystatin A1 and Its Amides: Effect on the In Vitro Activity, Cytotoxicity and Permeabilization of Model Membranes - Olga Omelchuk; Elena Bychkova; Svetlana Efimova; Natalia Grammatikova; George Zatonsky; Lyubov Dezhenkova; Svetlana Solovieva; Olga Ostroumova; Anna Tevyashova; Andrey Shchekotikhin (Antibiotics)
Objectives: In 2022, the World Health Organization highlighted the necessity for the development of new antifungal agents. Polyene antibiotics are characterized by a low risk of drug resistance; however, their use is limited by low solubility and severe side effects. Methods: A series of N-alkylated derivatives of amphotericin B and nystatin A1 as well as their N-(2-hydroxyethyl)amides were synthesized. Their antifungal activity was evaluated against various Candida strains and Aspergillus fumigatus using the broth microdilution method. Cytotoxicity was assessed using an MTT assay on human embryonic kidney cells HEK293 and human skin fibroblast cells hFB-hTERT6, as well as a hemolysis assay on erythrocytes. Membrane activity was analyzed by fluorimetric measurement of calcein leakage from model liposomes. Results: Derivatives containing the N-(hydroxyethyl)amino)ethyl fragment (compounds 3 and 4) exhibited relatively high antifungal activity, as did N-(2-hydroxyethyl)amides 5 and 9. Bis-modified compounds 6 and 10 did not outperform their mono-modified analogues in terms of activity or cytotoxicity. The mono-N-alkylated compound 3 showed the highest activity/toxicity ratio, which correlated well with its selectivity for ergosterol-containing model membranes. Discussion: Combining two successful modifications does not necessarily improve the activity/toxicity ratio of polyenes. Further studies can be performed for the optimization of carboxyl group of 3.